Management strategies for sustainability, new knowledge innovation, and personalized products and services - Pejić-Bach, Mirjana; Dogru, Caglar, 1983- (Advances in logistics, operations, and management science (ALOMS) book series., 2022)
"This reference book brings together the emerging topics of digital transformation, new knowledge innovation, sustainability, personalized products and services, advances in information technologies, new management strategies and digital practices in human resources and new forms of work"--